Experimental Investigation on the Effect of Size and Pitch of Hydrophobic Square Patterns on the Pool Boiling Heat Transfer Performance of Cylindrical Copper Surface - Sujith Kumar C. S. (Inventions, 2018)
In this work, pool boiling heat transfer tests were conducted for investigating the effects of the size and pitch of the hydrophobic square patterns on a copper test piece with the following dimensions: 40 mm long, 25 mm outer diameter, and 18 mm inner diameter. The size of the square patterns and the pitch were varied with an increment of 0.5 mm from 1 mm to 3 mm and from 4.5 to 5.5 mm, respectively. Among the various square patterns of different size and pitch, the 2 mm size square pattern with 5 mm pitch (inter-distance 3 mm) was found to be the best because it gives the advantage of bubble coalescence behavior and also the rewetting phenomenon. The observed bubble departure diameter was 2.35 mm, and using this diameter, we predicted the maximum inter-distance between the patterns for producing inter coalescence of bubbles in the axial direction was 3.12 mm. Therefore, a side-by-side distance of 3 mm, which was closed to the estimated inter-distance graphically, can avoid the earlier inter coalescence of the bubbles between patterns on the surface in the axial direction. This results in better pool boiling heat transfer performance. Highlights: (1) Heterogeneous wettable structures were obtained on the copper surface using screen printing techniques; (2) The effect of the size and pitch of the hydrophobic patterns on the bubble dynamics was determined; (3) The wall superheats of all the heterogeneous wettable surfaces were less than the plain copper surface; (4) The highest heat transfer coefficient was obtained from the hydrophobic pattern with 2 mm size and 5 mm pitch.